Respostas
respondido por:
1
questão :46
letra (a)
5⁴ . 5⁻³ =
( 5 )⁴⁻³ =
5¹ *** ( soma 3 expoentes)
letra (b)
2⁻³ / 2⁻¹ =
2⁻³ ⁻⁽⁻¹⁾ =
2 ⁻³⁺¹ =
2⁻² =
( 1/2)² =
1/4 ( diminui expoentes )
letra (c)
( 7⁴ )⁻³ =
( 7 )⁻¹² =
( 1/7)¹²
letra (d)
( -6)⁻³ . ( - 6)⁻² =
( - 6)⁻³⁻² =
( -6)⁻⁵ =
(- 1/6)⁵
letra (e)
( -1/2 )⁻⁴ : ( -1/2 )⁻¹ =
( - 1/2)⁻⁴⁻ ⁽ ⁻¹⁾ =
( - 1/2)⁻⁴⁺¹ =
( - 1/2)⁻³ =
( -2)³
letra (f)
( 3)⁻² . ( 3 )⁻⁵ : ( 3 )⁻¹ =
( 3 )⁻²⁻⁵ : ( 3 )⁻¹ =
( 3 )⁻⁷ : ( 3 )⁻¹ =
( 3 )⁻⁷⁻⁽⁻¹⁾ = ( 3 )⁻⁷⁺¹ =
( 3 )⁻⁶ = ( 1/3)⁶
LeticiaMartins65:
Obrigado
Perguntas similares
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás